Synthesis of spirocyclic Δ4-isoxazolines via [3 + 2] cycloaddition of indanone-derived ketonitrones with alkynes. Issue 48 (13th September 2021) - Liu, Yilin; Liu, Jiaxue; Liu, Yan-Yun; Tang, Boxiao; Lin, Hongwei; Li, Yuanxiang; Zhang, Lin
Abstract : A [3 + 2] cycloaddition of indanone-derived nitrones with alkynes under mild conditions has been developed. It is a highly efficient and straightforward method for the synthesis of diverse spirocyclicindenyl isoxazolines. Abstract : A [3 + 2] cycloaddition of indanone-derived nitrones and alkynes under mild conditions is developed, allowing facile synthesis of spirocyclicindenyl isoxazolines with structural diversity. The sequential protocol of generated in situ ketonitrone from unsaturated ketones and N -alkylhydroxylamines is also achieved successfully, affording the desired products in considerable yield with moderate to good diastereoselectivity. Moreover, the spirocyclic product can be conveniently transformed into indenyl-based allylic alcohol and enamide.